PENGARUH KEKERASAN DALAM RUMAH TANGGA TERHADAP PRESTASI ANAK DESA WONOSARI TIMUR - Laili, Laili; Juliana, Anggun (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This research is motivated by the influence of domestic violence on the achievements of the children of Wonosari Timur Village. With the formulation of the problem of this study is the large influence of domestic violence on the achievement of children in East Wonosari Village, What are the inhibiting factors that make violence in the household on the achievement of children in East Wonosari Village, The purpose of the problem of this study is: To determine the effect of violence in the household on the achievements of East Wonosari village children, to find out the inhibiting factors that make the influence of domestic violence on the achievements of East Wonosari village children. The method in this study is a quantitative method with data collection, namely using questionnaires, observation, and documentation. The data analysis technique used was regression analysis, with a total population of 184 households in this study and a sample of 36 residents. Based on the results of the research that the authors describe, it shows that there is an effect of domestic violence on children's achievement. This is evidenced by the t-value of -2.071 compared to the t-table of 1.697. Therefore, domestic violence has a fairly strong influence on the achievements of the children of Wonosari Timur Village